Inhibition of Inosine-5′-monophosphate Dehydrogenase from Bacillus anthracis: Mechanism Revealed by Pre-Steady-State Kinetics - Wei Y.; Kuzmič P.; Yu R.; Modi G.; Hedstrom L. (My University, 2025)
Inosine-5′-monophosphate dehydrogenase (IMPDH) catalyzes the conversion of inosine 5′-monophosphate (IMP) to xanthosine 5′-monophosphate (XMP). The enzyme is an emerging target for antimicrobial therapy. The small molecule inhibitor A110 has been identified as a potent and selective inhibitor of IMPDHs from a variety of pathogenic microorganisms. A recent X-ray crystallographic study reported that the inhibitor binds to the NAD+ cofactor site and forms a ternary complex with IMP. Here we report a pre-steady-state stopped-flow kinetic investigation of IMPDH from Bacillus anthracis designed to assess the kinetic significance of the crystallographic results. Stopped-flow kinetic experiments defined nine microscopic rate constants and two equilibrium constants that characterize both the catalytic cycle and details of the inhibition mechanism. In combination with steady-state initial rate studies, the results show that the inhibitor binds with high affinity (Kd ≈ 50 nM) predominantly to the covalent intermediate on the reaction pathway. Only a weak binding interaction (Kd ≈ 1 μM) is observed between the inhibitor and E·IMP. Thus, the E·IMP·A110 ternary complex, observed by X-ray crystallography, is largely kinetically irrelevant. © 2016 American Chemical Society.